Microstructure and Tensile behaviour of Thixocast LM25 Alloy: Effect of processing temperature - A K Tuli (Innovative Research Thoughts, 2017)
In the present work, microstructure and mechanical properties of thixocast LM25 alloy were correlated and linked with gravity cast LM25 alloy having the same composition. Thixocasting of samples was done at 590°C, 600°C and 610°C within a cylindrical die. Microstructures and mechanical properties were observed, correlated and compared with those of gravity cast samples. The yield strength, hardness, tensile strength and percentage elongation of the thixocast samples found to be greater than those of gravity cast samples. Improved mechanical properties of thixocast samples are due to non-dendritic globular structure and morphology of silicon particles.